Integrated approach of Pain management in Avabahuka (Frozen Shoulder)-A Case Study - Yadav, Pratima; Pandey, Anil Kumar (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: Avabahuka is a disease that usually affects the Amsa Sandhi (shoulder joint) & it is caused by the vitiated Vata Dosha. The term "Avabahuka" is not mentioned in the Vata Nanatmaja Vyadhi, but Acharya Sushruta and others have considered Avabahuka as a Vataja Vikara. Amsa Shosha, Shira Aakunch, and Baahupraspanditaharam symptoms are present in Avabahuka.. On the basis of signs and symptoms, Avabahuka can be co-related to frozen shoulder. Restrictions of glenohumeral movement are characteristic of this disease. Both passive and active shoulder movements are painfully restricted by frozen shoulder. Material & method: A female patient aged 38 years known case of Diabetes mellitus since 3 years reported with complaint of pain and difficulty in moving right upper limb. For the last 2 years, she was unable to move right upper limb due to pain and stiffness. Investigation: CBC, blood glucose, plain x-ray of the right shoulder joint etc. Treatments such as Abhyanga with Mahanarayana Tail, Patra Potli Pinda Sweda, Nasya with Anu Tail. Other treatment- Pendulum, shoulder wheel, and pulley exercises are examples of motion-stimulating exercises. Observation and Result: The patient had significant relief in pain and stiffness. After using Panchakarma procedure and some exercises, the full range of shoulder movement is present. Conclusion: By using Panchakarma procedures such as Patra Potli Pinda Sweda and Anu Tail Nasya, the patient does her daily routine work without any restrictions. The VAS (Visual Analogue Scale) pain score is used for the assessment of pain.